Implementation of Stunting Reduction Policy in Garut Regency - Srimulyani, Yani; Kania, Ikeu; Rismayanti, Ema (ann4publisher@gmail.com, 2024)
The problem of stunting in Garut Regency is very high at the district level, West Java Province. In-depth researchers 3 (three) research problems: (1) policy implementation, (2) efforts made, and (3) obstacles in program implementation. Therefore, the objectives of this study are: (1) describe the implementation of stunting reduction policies; (2) medicalize the efforts made as well; (3) obstacles/obstacles in implementation. This research uses qualitative methods, discussed and analyzed using the implementation of Marile S. Grindle's model policy. From the research activities carried out, researchers found: 1) There are several policies issued by the Garut Regency Government; 2) The existence of TPPS, TPK, and the Task Force for Handling Stunting; 3) There are 8 Scope of Service for intervention programs; 4) the existence of the Stunting Search Month Movement and implementing the TOSS program; 5) There are obstacles/obstacles in its implementation. Namely: (1) Family apathy indicated by stunting; (2) Lack of Optimal Coordination and Communication at the Implementation Level; (3) Limited human resources and not optimal capacity owned; (4) Limited budget and facilities/facilities. The research that has been carried out concluded that the Garut Regency government had implemented a policy to reduce stunting rates by issuing regulations and forming implementing organs, namely TPPS, TPK, the Stunting Task Force, universities, and other community organizations. The Garut Regional Government has provided human resources, budgets, and facilities/facilities to support the program's implementation. Some obstacles arise in the implementation of activities.